The Principle of Meritocracy in the Management Structure of Badan Pengelola Investasi (BPI) Danantara - Nurafifah, Yamuna; Pitra, Hajrazul (Al-Daulah: Jurnal Hukum dan Perundangan Islam, 2025)
BPI Danantara was established as a state-owned legal entity to manage SOEs' assets and investments, adopting the principle of meritocracy, similar to Temasek Holdings in Singapore. Normatively, the recruitment and appointment of officials is expected to be based on competence and professionalism. This research is a normative legal research using conceptual approaches and legislative approaches. The results of this study show a gap between the ideal of meritocracy and BPI Danantara's institutional practices. Through a comparative approach and normative analysis of Law 1/2025 and PP 10/2025, this study found that the institutional design and recruitment mechanism of BPI Danantara still opens room for political influence, both through the involvement of political actors in supervisory and executive organs and through the pattern of employee placement from ASN and SOEs. This finding confirms that meritocracy in BPI Danantara has not been fully institutionalized and continues to intersect with politicized practices in state investment governance.